Education in Malaysia : developments, reforms and prospects - Adams, Donnie (Abingdon, Oxon ; New York, NY : Routledge, 2023)
'This book examines Malaysia's ambitious reform agenda and educational landscape, drawing upon the eleven key shifts in the Malaysia Education Blueprint 2013-2025. It provides a comprehensive plan for a rapid and sustainable transformation of the Malaysian education system, and what is needed in shaping the educational reforms in Malaysia, especially post-COVID, through to 2025. The contributors to this volume - scholars, researchers and practitioners who possess a deep and embedded understanding of Malaysian education - focus on the interplay of prevailing and persistent problems, and what is needed in shaping the educational reforms in Malaysia. As a critical assessment of the Malaysian Education Blueprint reform efforts and policies, this edited book will be of particular interest to educators, scholars, and policymakers on the latest trends and challenges in Malaysian education policy'--
Malaysian education system : progress, standards, and aspirations / Donnie Adams and King Lok Tan -- Gender equity and the'Lost Boys' in Malaysian education / Mohammad Noman and Amrita Kaur -- Education transformation of Orang Asli students in Malaysia / Ahmad Zabidi Abdul Razak -- The gifted and talented education programme in Malaysia : development, reform, and way forward / Abu Yazid Abu Bakar and Zulkarnin Zakaria -- Minding the gap between theory and practice to reinforce the delivery of STEM education / Mageswary Karpudewan -- Notable new navigations of Malaysian English language education / Adelina Asmawi -- Quality preschool education for human capital development / Husaina Banu Kenayathulla, Mohd Nazri Abdul Rahman, and Muhammad Faizal A. Ghani -- Transformation of Islamic education for values-driven Malaysians / Norfariza Mohd Radzi and Zetty Nurzuliana Rashed -- Fostering national unity in Malaysia : the roles of family and education / Intan Marfarrina Omar, Ahmad Zabidi Abdul Razak, and Faridzah Jamaluddin -- Moral education and Islamic education : the way forward towards a value-laden society / Vishalache Balakrishnan -- ICT in Malaysian education : preparations and milestones / Kenny S.L Cheah -- Technical and vocational education and training in Malaysia : reflections, recognition, and renaissance / Donnie Adams and Kenny S.L Cheah -- Empowering educators to transform learning and teaching / Donnie Adams and Suzieleez Syrene Abdul Rahim -- Leadership practices of high performing school principals in Malaysia / Zuraidah Abdullah, Ahmad Zabidi Abdul Razak, and Kazi Enamul Hoque -- Vernacular schools and national unity in a multicultural society / Wendy Yee Mei Tien and Hazri Jamil -- Education transformation in Malaysia : equity, funding, and strategic partnership / Zuliana Mohd Zabidi and Donnie Adams.
OCLC-licensed vendor bibliographic record.
Keywords: Education -- Malaysia; Educational change -- Malaysia; Education and state -- Malaysia